SPATIAL DISTRIBUTION STUDY OF SPECIE SCORODOPHLOEUS ZENKERI HARMS (FABACEAE) IN YOKO RESERVE AND BIARO FOREST (UBUNDU, DEMOCRATIC REPUBLIC OF CONGO) - Lomba, Christophe B.; NDJELE, M. B; PICARD, N (IJRDO-Journal of Applied Science, 2022)
A study based on spatial distribution of Scorodophloeus zenkeri was performed in the device 400ha Biaro forest. Both specie has multiple uses, including industrial exploitation by the quality of wood.An inventory of the forest potential of these  specie were made based on values in abscissa (x) and ordonna  (y) for all individuals. At  the end of this inventory, 9115  feet were counted with 9098 feet  at reserve Yoko and 17 individuals at Biaro forest. The spatial distribution of individuals of both specie is aleator type  at reserve Yoko and  aggregated type at Biaro forest.